The clinical value of CT and MRI in preoperative TNM staging of esophageal cancer - Zhao, Weijun; Huang, Jing; Chen, Yukun; Lu, Jingjing; Hu, Wentao (Frontiers in Medicine, 2025)
ObjectiveTo evaluate and compare the clinical value of computed tomography (CT) and magnetic resonance imaging (MRI) in the preoperative TNM staging of esophageal carcinoma.MethodsA total of 1,209 patients with histologically confirmed esophageal cancer who underwent preoperative CT (n = 868) or MRI (n = 341) scanning from January 2014 to December 2024 were retrospectively analyzed. Tumor location, histologic type, and postoperative pathological TNM stage were recorded. CT and MRI findings were compared with pathological results as the standard.ResultsFor T-stage, the overall accuracy of CT was 86%, with a sensitivity and specificity of 53 and 89%, respectively. MRI achieved an accuracy of 82%, with sensitivity and specificity of 57 and 93%, respectively. For N-stage, CT showed a sensitivity, specificity, and accuracy of 85, 83, and 84% for mediastinal lymph nodes, and 87, 82, and 83% for abdominal lymph nodes. There was no significant difference in the total accuracy rate of TN staging diagnosis of esophageal cancer between the two groups.ConclusionBoth CT and MRI demonstrate high diagnostic value in the preoperative TNM stage of esophageal carcinoma. While CT is more economic and easier to operate, MRI offers superior contrast of connective tissues and multiplanar imaging, making it particularly valuable in evaluating T4 stage and assessing tumor invasion of adjacent organs. Limitations exist in early T-stage and N-stage assessments due to difficulty distinguishing mucosal infiltration and differentiating metastatic from non-metastatic lymphadenopathy. Multimodal imaging strategies and tumor-targeted contrast agents may enhance staging precision.